"If only you were a boy…": Friendship and sexual identity in Mireille Best's Hymne aux Murènes. Issue 1 (2nd January 2018) - Schechner, Stephanie
ABSTRACT: While much French fiction devoted to lesbians focuses on romantic relationships, Mireille Best's (1943–2005) first novel, Hymne aux Murènes ( Hymn to the Moray Eels ) (1986), depicts a wide variety of relationships between the lesbian protagonist, Mila, and the other young women staying in a sanatorium of sorts for the treatment of an unnamed illness. In this all-female environment, Best depicts relationships between Mila and Paule, a closeted lesbian employee of the sanatorium; between Mila and young women like Josette and Lilli, who are somewhat attracted to Mila but, for the most part, do not act on this attraction; and between very close heterosexual friends (Nicoli and Nicola). In so doing, Best expands the reader's notion of friendship between women and blurs the lines between lesbians and heterosexuals, guiding the reader toward a more complex understanding of female friendship in general and lesbian friendship in particular. Throughout the novel, several characters express frustration about Mila's gender identity by saying, "If only you were a boy…" While Mila remains romantically frustrated, she develops close friendships with several young women, and Best thus conveys optimism about lesbians' ability to form friendships during adolescence and early adulthood, a time of life when, according to her characters, the boundaries between heterosexuality and lesbianism seem less rigid than they might be later in life. In this essay, I focus primarily on Best's first novel, but I include brief reflections on an earlier short story that echoes the presentation of lesbians and friendship found in the novel.